Pengaruh Penyaluran Kredit Hijau dan Capital Adequacy Ratio terhadap Kinerja Keuangan dengan Risiko Kredit sebagai Variabel Intervening pada Bank Konvensional - Hana Tamara Putri; Fadil Iskandar; Ahmadi Ahmadi; Muhammad Ade Masyhuri; Kenny Febrian (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
This study aims to analyze the direct and indirect effects of green credit and the capital adequacy ratio (CAR) on financial performance as measured by return on equity (RoE), through credit risk as measured by non-performing loans (NPL) in conventional banks listed on the Indonesia Stock Exchange. This study uses a quantitative method utilizing secondary data obtained from company annual reports. The research sample consists of 10 conventional banks listed on the Indonesia Stock Exchange, selected using a purposive sampling technique from a population of 22 banks during the 2020–2024 period. The results show that there are direct and indirect effects between green credit and the capital adequacy ratio on credit risk and financial performance, as well as direct and indirect effects of green credit and the capital adequacy ratio on financial performance mediated by credit risk in conventional banks listed on the Indonesia Stock Exchange.